2010
DOI: 10.1002/anie.201001866
|View full text |Cite
|
Sign up to set email alerts
|

Bis(1,3‐trimethylsilylallyl)beryllium

Abstract: Shape‐shifter: The beryllium allyl complex [Be{1,3‐(SiMe3)2C3H3}2(Et2O)] (see picture) has been synthesized and its X‐ray structure determined. Although the allyl ligands are σ bonded, the molecule is fluxional in solution, and it engages in a Schlenk equilibrium with BeCl2. DFT calculations suggest that in the absence of a coordinated base, both σ‐ and π‐bound forms would be potential energy minima.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Treatment of BeCl 2 with potassium 1,3-bistrimethylsilylallyl in Et 2 Og ave the s-bound allyl-beryllium complex 34.T his compound exhibits fluxional behavior in solution and provided the first evidence for Schlenk type equilibria in beryllium organyls. [44] Salt-metathesis reactions of BeCl 2 or BeBr 2 with one equivalent of ab ulky lithium aryl in diethyl ether leads to threefold-coordinated complexes in whicho ne aryl, one halide, and one ether molecule are bound to the beryllium atom. Introduction of as terically demanding amido ligand then gives the twofold-coordinated linear compound 35.…”
Section: C-donor Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of BeCl 2 with potassium 1,3-bistrimethylsilylallyl in Et 2 Og ave the s-bound allyl-beryllium complex 34.T his compound exhibits fluxional behavior in solution and provided the first evidence for Schlenk type equilibria in beryllium organyls. [44] Salt-metathesis reactions of BeCl 2 or BeBr 2 with one equivalent of ab ulky lithium aryl in diethyl ether leads to threefold-coordinated complexes in whicho ne aryl, one halide, and one ether molecule are bound to the beryllium atom. Introduction of as terically demanding amido ligand then gives the twofold-coordinated linear compound 35.…”
Section: C-donor Ligandsmentioning
confidence: 99%
“…Beryllium organyls, beryllium-carbenea nd carbodiphosphorane complexes (Mes = 2,4,6-Me 3 C 6 H 2 ;dipp = 2,6-iPr 2 C 6 H 3 ). [25,26,38,39,41,44] Chem.E ur.J. 2019, 25,12018 -12036 www.chemeurj.org bond order of 1.5.…”
Section: C-donor Ligandsmentioning
confidence: 99%
“…[23] These resonances are clearly different from those in the more complex spectrum of [{MgA' 2 } 2 ], which reflect monomer-Qdimer rearrangement in solution. [7] Crystals of 1 suitable for X-ray crystal diffraction were originally grown from as lowly evaporated toluene solution, and although they ultimately yielded as tructure of connectivity-only quality (Figure 3), several features are worth noting. Thec omplex is at rimetallic monomer with af undamental composition of 2:1:4K/Mg/A',which does not reflect the reagent stoichiometry.One allyl ligand is found h 1 -bonded to the Mg center.…”
Section: Resultsmentioning
confidence: 99%
“…[6] However,f or the Group 2metals,only alimited range of bonding patterns has been documented. To date,b eryllium compounds have been found with s-bound (h 1 )( Figure 1a) [7] and m 2 -h 1 ,h 2 allyls (Figure 1h). [8] In contrast, with very rare exceptions, h 3conformations are uniformly the norm with complexes of the heavier alkaline-earth metals (Ca-Ba).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with studies that showed that for some fluxional beryllium allyl complexes, recently synthesized, both σ-and π-bound forms would be potential energy minima. 54 It is worth noting that although for BH 3 containing complexes the value of Δ r G 1 0 for the ethynyl containing systems is smaller in absolute value than for the vinyl containing analogues, in all cases the formation of the complexes is predicted to be exergonic.…”
Section: Acidity Enhancementmentioning
confidence: 90%